Optimization of handover algorithms in 3GPP long term evolution system - Lin, Cheng-Chung; Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Basukala, Riyaj; Patachaianand, Rachod; Chen, Lu; Afrin, Toyoba Sohana (IEEE, 2011)
Handover in LTE is purely hard handover. The use of break-before-connect handovers reduces the complexity of the LTE network architecture. However, the hard handover may result in data being lost. A Handover algorithm is needed for making handover decision. This decision may vary over time, depending on user’s mobility. Many handover algorithms have been proposed. In this work, we optimized three well known handover algorithms in the LTE system. Simulation results show that this optimization outperforms non-optimized algorithms by minimizing the average number of handovers per UE per second while maximizing average system throughput.